Biofilm formation, sodium hypochlorite susceptibility and genetic diversity of Vibrio parahaemolyticus - Wang D; Fletcher GC; On SLW; Palmer JS; Gagic D; Flint SH (Elsevier BV, 2023)
Vibrio parahaemolyticus is a marine oriented pathogen; and biofilm formation enables its survival and persistence on seafood processing plant, complicating the hygienic practice. The objectives of this study are to assess the ability of V. parahaemolyticus isolated from seafood related environments to form biofilms, to determine the effective sodium hypochlorite concentrations required to inactivate planktonic and biofilm cells, and to evaluate the genetic diversity required for strong biofilm formation. Among nine isolates, PFR30J09 and PFR34B02 isolates were identified as strong biofilm forming strains, with biofilm cell counts of 7.20, 7.08 log10 CFU/cm2, respectively, on stainless steel coupons after incubation at 25 °C. Free available chlorine of 1176 mg/L and 4704 mg/L was required to eliminate biofilm cells of 1.74-2.28 log10 CFU/cm2 and > 7 log10 CFU/cm2, respectively, whereas 63 mg/L for planktonic cells, indicating the ineffectiveness of sodium hypochlorite in eliminating V. parahaemolyticus biofilm cells at recommended concentration in the food industry. These strong biofilm-forming isolates produced more polysaccharides and were less susceptible to sodium hypochlorite, implying a possible correlation between polysaccharide production and sodium hypochlorite susceptibility. Genetic diversity in mshA, mshC and mshD contributed to the observed variation in biofilm formation between isolates. This study identified strong biofilm-forming V. parahaemolyticus strains of new multilocus sequence typing (MLST) types, showed a relationship between polysaccharide production and sodium hypochlorite resistance.
Keywords: Biofilm; Genomic feature; Multilocus sequence typing (MLST); Sodium hypochlorite; Whole genome sequencing (WGS); Vibrio parahaemolyticus; Sodium Hypochlorite; Multilocus Sequence Typing; Biofilms; Genetic Variation